The role of stickiness, extrapolation and past consensus forecasts in macroeconomic expectations - Hagenhoff, Tim; Lustenhouwer, Joep (Discussion paper series, 2020)
We propose a simple model of expectation formation with three distinct deviations from fully rational expectations. In particular, forecasters' expectations are sticky, extrapolate the most recent news about the current period, and depend on the lagged consensus forecast about the period being forecast. We find that all three biases are present in the Survey of Professional Forecaster as well as in the Livingston Survey, and that their magnitudes depend on the forecasting horizon. Moreover, in an over-identified econometric specification, we find that the restriction on coefficients implied by our model is always close to being satisfied and in most cases not rejected. We also stress the point that using the past consensus forecast to form expectations is a rather smart thing to do if cognitive limitations and biases cause any attempt to build an own rational forecast to fail.
Keywords: Graue Literatur